2016
DOI: 10.7454/jki.v19i1.428
|View full text |Cite
|
Sign up to set email alerts
|

Masalah Tidur dan Strategi Koping pada Perawat Di Rawat Inap

Abstract: AbstrakMasalah tidur merupakan masalah yang sering dialami oleh orang dewasa, termasuk perawat yang bekerja dengan sistem shift di ruang rawat inap. Koping adaptif diperlukan untuk mengatasi masalah tidur tersebut. Penelitian ini bertujuan untuk memeroleh gambaran masalah tidur dan strategi koping perawat dalam mengatasi masalah tidurnya. Penelitian deskriptif ini dilakukan dengan melibatkan 106 perawat rawat inap yang diplih dengan cluster proportional sampling di salah satu Rumah Sakit di Jakarta. Modifikasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, numerous studies conducted in Taiwan, Iran, America found that suffered from poor sleep and generally less than general population as cited by Sun, Ji, Zhou, and Liu (2018). In a study conducted by Rahmi and Kuntarti (2016) employing 106 clinical nurses who work at a hospital in Jakarta found that nurses have problems covered insomnia (30.2%), sleep apnea (14.2%), restless legs syndrome (10.4%), and narcolepsy (10.4%). Studies also suggested that average sleep durations have decreased from 9 hours in 1910 to as little as 6.9 hours on workdays in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies conducted in Taiwan, Iran, America found that suffered from poor sleep and generally less than general population as cited by Sun, Ji, Zhou, and Liu (2018). In a study conducted by Rahmi and Kuntarti (2016) employing 106 clinical nurses who work at a hospital in Jakarta found that nurses have problems covered insomnia (30.2%), sleep apnea (14.2%), restless legs syndrome (10.4%), and narcolepsy (10.4%). Studies also suggested that average sleep durations have decreased from 9 hours in 1910 to as little as 6.9 hours on workdays in 2002.…”
Section: Introductionmentioning
confidence: 99%